Study of the cluster formation in low-temperature systems. Spectral manifestation of resonance dipole-dipole interactions between nondipole polyatomic molecules - Cherevatova, A.N.; Bocharov, V.N.; Kolomiitsova, T.D.; Shchepkin, D.N.; Tokhadze, K.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Resonance dipole–dipole interactions are shown to strongly manifest themselves in fundamental and overtone band shapes of low-temperature systems, consisting of polar and nonpolar molecules as well with a relatively large first derivatives (P′ > 0.3 D) of the dipole moment. The rough model on the basis of the interaction between two non-degenerate, doubly degenerate, and triply degenerate oscillators was developed to study pairs of interacting molecules and clusters in low-temperature condensed systems. The concentration dependences of second- and third-order spectral band moments permitted the number of molecules in clusters to be estimated.